PENGARUH UPAH, PERTUMBUHAN EKONOMI , INFLASI DAN TINGKAT SUKU BUNGA TERHADAP INVESTASI DI PROVINSI MALUKU - Muhammad Dahlan Sely (Jurnal Cita Ekonomika, 2019)
This study was conducted to determine the Effect of Wages, Economic Growth, Inflation and Interest Rates on Investment in the Provinces in 1998 - 2018. Variables used in this study are wages, economic growth, inflation and interest rates as independent variables and investment as dependent variables. The data used in this study are secondary data sourced from the Central Statistics Office of the Maluku province, the Office of Investment and Integrated Services of the One Door Province of Maluku, Economic and Financial Statistics of Indonesia-Bank Indonesia and the Office of the Regional Development Planning Agency. The data used are time series data from 1998 to 2018. The analytical method used is multiple regression analysis using the classical assumption test. Based on the four classical assumptions tests, namely tests of normality, multicollinearity, heteroscedasticity and autocorrelation, no variables were found that deviate from the classical assumptions. The results showed that the variable of economic growth had a positive and significant effect on investment in the Maluku province. Variable wage rates and economic growth have a positive and significant effect on investment in Maluku province. Inflation variable has a significant positive effect on Investment in Maluku Province. Variable interest rates have a negative and significant effect on investment in Maluku Province. The coefficient of determination is 0.794984, this number implies that the investment variable in this study can be explained by the variable variable, economic growth, inflation and interest rates of 79.49% while the remaining 20.51% is explained by other variables outside this research model.